Coordination in parental effort decreases with age in a long‐lived seabird. Issue 12 (22nd September 2020) - Patrick, Samantha C.; Corbeau, Alexandre; Réale, Denis; Weimerskirch, Henri
Abstract : Biparental care is widespread in avian species. Individuals may match the contribution of their partner, resulting in equal parental effort, or may exploit their partner, to minimise their own investment. These two hypotheses have received much theoretical and empirical attention in short‐lived species, that change mates between seasons. However, in species with persistent pair bonds, where divorce is rare and costly, selective pressures are different, as partners share the value of future reproduction. In such species, coordination has been suggested to be adaptive and to increase early in life, as a consequence of the importance of mate familiarity. However, as birds age, an increase in re‐pairing probability occurs in parallel to a decline in their survival probability. At the point when partners no longer share future reproductive success, exploitation of a partner could become adaptive, reducing selection for coordinated effort. As such, we suggest that coordination in parental effort will decline with age in long‐lived species. Using incubation bout duration data, estimated from salt‐water immersion bio‐loggers, deployed on black‐browed albatrosses Thalassarche melanophris, we examined the correlation in incubation bout durations for sequential bouts, as a measure of coordination. Our results show that coordination is highest in inexperienced pairs (early in reproductive life) and declines throughout the lifetime of birds. This suggests that both cooperation, indicated by coordinated effort, and conflict over care occurs in this species. We find no change in individual bout duration with increasing breeding experience, and hence no support for the hypothesis that aging leads to changes in individual incubation behaviour. This is, to our knowledge, the first study to demonstrate strong coordination in parental care when pairs share future reproductive success, but a decline in coordination with age, as sexual conflict increases.